The Effectiveness of TMLM on Student Teachers’ Personality and Social Competence measured with Teacher Competency Assessment in the COVID-19 Pandemic Era - Ririn Ambarin; Abdurrachman Fairidi; Sukarno Sukarno; Issy Yuliasri (Faculty of Teacher Training and Education, Mulawarman University, 2021)
Many pre-service education microteaching projects are aiming to address a range of difficulties that future teachers face in a variety of teaching situations while also enhancing the overall value of the teacher education program. Microteaching is another sort of teacher performance training that restricts the components of the learning process so that prospective teachers can master teaching skills and components one at a time in a smaller teaching environment. The TADALURING Microteaching Learning Paradigm (TMLM) is a microteaching learning model that comprises of three complimentary teaching practices: classroom, online, and offline practice. A study of TMLM was conducted with 20 teacher students in Magang 2 course on how to teach. Between pre - tests and post competency, participants' personalities and social competence developed. The objective of this study is to assess how effective TMLM is at increasing student teachers' personality and social skills as measured by Teacher Competency Assessment. Data collection techniques include observation, interview, questionnaire, recording, and testing of the study's findings. The data is analyzed with SPSS. Using a one-group pretest–posttest strategy, field testing was done in the field. The outcomes of student learning tests were analyzed using the t-test method (paired samples test). In the COVID-19 Pandemic Era, the effectiveness of the Tadaluring Microteaching Learning Model on Student Teachers' Personality and Social Competence as measured by Teacher Competency Assessment revealed that the average results of the experimental class after using the Tadaluring Microteaching Learning Model developed of 87.9795 amounted to 82.6025. These findings show that the microteaching approach developed can help student teachers enhance their personalities and social abilities.